Level of chemical element content in serum of thyroid cancer patients as a potential biomarkers for thyroid cancer - Jaafar, Zahraa Ali (Edelweiss Applied Science and Technology, 2025)
The thyroid gland plays a crucial role in regulating metabolism and growth through the production of thyroid hormones. Trace elements are vital for the proper functioning of the thyroid and are implicated in various thyroid disorders, including autoimmune diseases and malignancies. Among these trace elements, iron (Fe), copper (Cu), manganese (Mn), zinc (Zn), and magnesium (Mg) have been closely studied for their impact on thyroid health. The imbalance or deficiency of these elements can interfere with thyroid function and potentially contribute to the development of thyroid pathologies. This study aimed to investigate the serum levels of several trace elements—zinc, copper, iron, manganese, and magnesium—in patients diagnosed with thyroid cancer, specifically comparing these levels with those in healthy controls. The primary objective was to identify any correlations between trace element concentrations and the occurrence of thyroid malignancies to understand their potential role in the development and progression of thyroid cancer. The study included 45 thyroid cancer patients, consisting of 31 individuals with papillary thyroid carcinoma (PTC) and 14 with follicular thyroid carcinoma (FTC), as well as 45 healthy controls. Serum concentrations of zinc, copper, iron, manganese, and magnesium were measured and compared between the two groups. Statistical analyses were performed to assess differences in the concentrations of these trace elements and to determine any significant relationships with thyroid cancer occurrence. The study found a statistically significant increase in the serum levels of copper and manganese in thyroid cancer patients compared to healthy controls (p < 0.05). Conversely, levels of zinc, iron, and magnesium were significantly lower in the cancer group. These findings indicate a strong association between altered trace element concentrations and the presence of thyroid malignancy, particularly copper and manganese, which were elevated in the serum of cancer patients. Furthermore, the data suggest that deficiencies in other trace elements, such as zinc, may also contribute to the pathophysiology of thyroid cancer. The results of this study highlight the potential role of trace elements, particularly copper and manganese, in thyroid cancer development. The observed alterations in trace element levels may serve as useful biomarkers for the diagnosis and prognosis of thyroid cancer. Further research is needed to explore the underlying mechanisms connecting trace element imbalances with thyroid malignancies and to develop targeted therapeutic strategies aimed at correcting these deficiencies to improve patient outcomes.